The Effects of Irreversible Electroporation (IRE) on Nerves - Li, Wei (Public Library of Science, 2011)
BACKGROUND: If a critical nerve is circumferentially involved with tumor, radical surgery intended to cure the cancer must sacrifice the nerve. Loss of critical nerves may lead to serious consequences. In spite of the impressive technical advancements in nerve reconstruction, complete recovery and normalization of nerve function is difficult to achieve. Though irreversible electroporation (IRE) might be a promising choice to treat tumors near or involved critical nerve, the pathophysiology of the nerve after IRE treatment has not be clearly defined. METHODS: We applied IRE directly to a rat sciatic nerve to study the long term effects of IRE on the nerve. A sequence of 10 square pulses of 3800 V/cm, each 100 µs long was applied directly to rat sciatic nerves. In each animal of group I (IRE) the procedure was applied to produce a treated length of about 10 mm. In each animal of group II (Control) the electrodes were only applied directly on the sciatic nerve for the same time. Electrophysiological, histological, and functional studies were performed on immediately after and 3 days, 1 week, 3, 5, 7 and 10 weeks following surgery. FINDINGS: Electrophysiological, histological, and functional results show the nerve treated with IRE can attain full recovery after 7 weeks. CONCLUSION: This finding is indicative of the preservation of nerve involving malignant tumors with respect to the application of IRE pulses to ablate tumors completely. In summary, IRE may be a promising treatment tool for any tumor involving nerves.